2006
DOI: 10.1117/12.662008
|View full text |Cite
|
Sign up to set email alerts
|

Application of a micromachined translatory actuator to an optical FTIR spectrometer

Abstract: We present a Fourier-transform infrared (FTIR) spectrometer where a micro-opto-electro-mechanical system (MOEMS) replaces the macroscopic mirror drive enabling a miniaturized, robust and low cost system. The MOEMS devices are manufactured in a CMOS compatible process on a silicon on insulator (SOI) substrate. The device consists of a metallized actuator plate with an area of 1.65 mm2 acting as mirror, bearing springs and electrodes for the electrostatic drive. Due to the driving principle based on in-plane ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…7͑b͔͒. exceed 90 m due to parasitic oscillation modes ͑e.g., outof-plane rotation mode͒. 13 An extrapolation of the results gives a required driving voltage of over 700 V at ambient pressure, which cannot be supported by the device due to the electromechanical stability of the comb drive.…”
Section: Amplitude Versus Frequency and Pressurementioning
confidence: 98%
“…7͑b͔͒. exceed 90 m due to parasitic oscillation modes ͑e.g., outof-plane rotation mode͒. 13 An extrapolation of the results gives a required driving voltage of over 700 V at ambient pressure, which cannot be supported by the device due to the electromechanical stability of the comb drive.…”
Section: Amplitude Versus Frequency and Pressurementioning
confidence: 98%
“…In the first tested layout (type A) of the translational micromechanical mirror, the actual mirror element is suspended on two long bending springs ( Figure 1) [4]. While allowing for high oscillation frequencies, this design showed a number of critical limitations.…”
Section: A Translational Mems Mirror Componentmentioning
confidence: 99%
“…In contrast with the design in [23,24], we assemble silicon and glass micro parts onto a Silicon-on-Insulator (SOI) die to accomplish scanning, collimation, and interference. A MEMS thermal Chevron actuator [27] is used for moving the scanning mirror.…”
Section: Introductionmentioning
confidence: 99%
“…Kung L. et al have shown a standing wave transform spectrometer [22] which uses an electrostatically actuated MEMS mirror with onresonance displacement of up to 65 µm, a thin-film photo-detector, and an electrical back plane for actuating the mirror. Fraunhofer Institute for Photonic Microsystems is developing Fourier Transform spectrometers for measurements from near IR to mid IR range [23,24]. The complete devices are around 10 cm×20 cm in size, and use in-plane electrostatic combs which are vacuumpackaged.…”
Section: Introductionmentioning
confidence: 99%